2019
DOI: 10.3390/w11040707
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Extreme Events in Precipitation, Stream Discharge, and Groundwater Head Fluctuation: Distribution, Memory, and Correlation

Abstract: Hydrological extremes in the water cycle can significantly affect surface water engineering design, and represents the high-impact response of surface water and groundwater systems to climate change. Statistical analysis of these extreme events provides a convenient way to interpret the nature of, and interaction between, components of the water cycle. This study applies three probability density functions (PDFs), Gumbel, stable, and stretched Gaussian distributions, to capture the distribution of extremes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…For precipitation, the transformation step is usually done by fitting a gamma distribution function to the data (Mc-Kee et al, 1993). For groundwater heads, however, distribution shapes vary widely between locations (Bloomfield and Marchant, 2013;Dawley et al, 2019;Loáiciga, 2015). Fitting individual parametric distribution functions to each location based on the 30-year monthly series used here is likely to give unreliable results; for example, Link et al (2020) found that more than 100 data points are needed for fitting reliable parametric distributions on hydrological series in most cases, while incorrect transformations give a high risk of biased drought index values (Svensson et al, 2017).…”
Section: Drought Indexmentioning
confidence: 96%
“…For precipitation, the transformation step is usually done by fitting a gamma distribution function to the data (Mc-Kee et al, 1993). For groundwater heads, however, distribution shapes vary widely between locations (Bloomfield and Marchant, 2013;Dawley et al, 2019;Loáiciga, 2015). Fitting individual parametric distribution functions to each location based on the 30-year monthly series used here is likely to give unreliable results; for example, Link et al (2020) found that more than 100 data points are needed for fitting reliable parametric distributions on hydrological series in most cases, while incorrect transformations give a high risk of biased drought index values (Svensson et al, 2017).…”
Section: Drought Indexmentioning
confidence: 96%
“…For precipitation, the transformation step is usually done by fitting a gamma distribution function to the data. For groundwater heads, however, distribution shapes vary widely between locations (Bloomfield and Marchant, 2013;Dawley et al, 2019;Loáiciga, 2015). It is possible to fit individual parametric distribution functions to the groundwater series, but the 30-year monthly series used here are probably insufficient to do this reliably (Link et al, 2020), giving a high risk of biased drought index values (Svensson et al, 2017).…”
Section: Drought Indexmentioning
confidence: 99%
“…Mahmud et al [12] 31 March 2018 2 4 1 1 Rhee and Yang [13] 14 June 2018 2 2 0 0 Khan et al [14] 27 July 2018 2 2 1 1 Mousavi et al [15] 16 October 2018 2 3 1 1 Amnatsan et al [16] 9 November 2018 3 3 0 0 Bafitlhile and Li [17] 6 January 2019 3 3 1 1 Pan et al [18] 22 January 2019 2 2 0 0 Ávila et al [19] 22 February 2019 4 5 2 1 Pham et al [20] 3 March 2019 3 3 1 1 Tung et al [21] 8 March 2019 2 2 0 0 Dawley et al [22] 5 April 2019 3 3 0 0 Zhang and Wang [23] 4 June 2019 2 5 0 0 Mehmood et al [24] 14 June 2019 3 5 0 0…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
“…The interconnection between hydrological extremes was addressed by Dawley et al [22] who correlated surface and subsurface hydrological extreme events by investigating the possible effects of extreme storm events of different properties on the fluctuations in surface and subsurface water systems. They applied three probability density functions (PDFs), Gumbel, stable, and stretched Gaussian distributions, to capture the distribution of extremes and the full-time series of storm properties (storm duration, intensity, total precipitation, and inter-storm period), stream discharge, lake stage, and groundwater head values.…”
Section: Case Studiesmentioning
confidence: 99%